Importance of boron for agriculture productivity: a review - Muhammad, Saleem; Yusop, Mohd Khanif; Ishak, Che Fauziah; Abd. Wahid, Samsuri; Hafeezullah, Babar (International Research Journals, 2011)
Boron is unique, not only in its chemical properties, but also in its roles in biology. Since boron discovery as essential plant nutrient, the importance of B element as an agricultural chemical has grown very rapidly and its availability in soil and irrigation water is an important determinant of agricultural production. Boron deficiency is the most common and widespread micronutrient deficiency problem, which impairs plant growth and reduces yield. Normal healthy plant growth requires a continuous supply of B, once it is taken up and used in the plant; it is not translocated from old to new tissue. That is why, deficiency symptoms starts with the youngest growing tissues. Therefore, adequate B supply is necessary for obtaining high yields and good quality y of agriculture crops.